(untitled) (Health Renaissance, 2017)
Introduction: Unstable dislocations of the bilateral glenohumeral joint with fractures of both greater tuberosities are very rare. Case presentation: A 48-year-old gentleman sustained a bilateral anterior dislocation of his glenohumeral joint with fractures of the greater tuberosities on both sides after an episode of seizure. Attitude of both shoulders were abducted and externally rotated. Radiological examination revealed the dislocations of bilateral glenohumeral joint and also the fractures of the bilateral greater tuberosities. Closed reduction and shoulder derotation immobilizer was applied. The Reduction was unstable and needed fixation of both sides greater tuberosity with cannulated cancellous screws. The shoulders were immobilized for 3 weeks and subsequent rehabilitation yielded a good outcome. Results at 6 months follow-up were satisfactory with normal range of motion and no redislocations occurring. To our knowledge, this is the first reported case of bilateral unstable glenohumeral joint dislocation associated with fractures of both greater tuberosities in a middle aged man which was unstable needing fixation of greater tuberosities fractures. Conclusion: Bilateral glenohumeral joint dislocations with bilateral fractures of the greater tuberosities may be unstable needing fixation of greater tuberosity fracture. Health Renaissance 2015;13(2): 173-177